A Child Girl Has Severe Case of Pediatric Atopic Dermatitis: Treatment with Terbinafine Hydrochloride - Ismail, Kenan Omar; Albawwab, Asem Mohammad Khader; Ayoub, Basel Mahmoud (Journal of medical and pharmaceutical sciences, 2022)
Atopic dermatitis in early childhood accounts for 20% of all atopic dermatitis occurrences, with similar atopic dermatitis symptomology of red pustules or scales characteristic. The potential causation of atopic dermatitis varies, may be hereditary in some cases. Combination topical therapies are used to treat patients with a compromised skin barrier. There are few safe and regulated pharmacotherapeutic atopic dermatitis therapies for pediatric use, and current treatment satisfaction is low. Here we provide details of the successful treatment of a pediatric patient with pustular atopic dermatitis using topical application of terbinafine hydrochloride in tandem with maternal diet control on July 22, 2020 at AYA Medical Center in Sydney, Australia. After a six-month follow-up, the patient’s symptoms had fully recovered. Thus, Terbinafine hydrochloride may be useful in the treatment of atopic dermatitis in children.